Peran Pesantren dalam Pengembangan Ekonomi Syariah - Abd Kholik; Abd Adim; Abd Hamid (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
This examines targets to analyze the position of Islamic boarding schools (pesantren) in the development of sharia economics in Indonesia. As Islamic educational institutions, pesantren not most effective serve as facilities for spiritual instruction but also have vast potential in fostering network monetary empowerment primarily based on sharia principles. This examination makes use of a qualitative approach with library studies strategies by reviewing various scientific literature, reputable journals, books, and related files that discuss sharia economics and the function of pesantren in economic empowerment. The results of this have a look at imply that pesantren have a strategic role in the development of sharia economics through numerous components, as follows: first, sharia economic education and literacy for students and the community; 2d, the development of pesantren-based totally entrepreneurship; 1/3, the control of sharia financial institutions such as sharia cooperatives or Baitul Maal wal Tamwil (BMT); and fourth, community economic empowerment through effective business units. Furthermore, pesantren also play a role as marketers of social change able to integrate Islamic values with equitable and sustainable monetary practices. With the capability of a vast community of Islamic boarding schools in Indonesia, strengthening the economic capacity of Islamic boarding schools can be a vital strategy in accelerating the growth and strengthening of the national sharia ecosystem.